Interventions to reduce arterial puncture-related pain: A systematic review and meta-analysis. (February 2022) - Gonella, Silvia; Clari, Marco; Conti, Alessio; Simionato, Laura; Tassone, Cristina; Berchialla, Paola; Campagna, Sara
Abstract: Background: Arterial puncture-related pain remains unaddressed across several clinical settings. Analgesic techniques are not routinely employed before arterial puncture despite the recommendation that local anesthesia be used, except in emergencies. A comprehensive review of interventions aimed at reducing arterial puncture-related pain and their potential effectiveness is lacking, and the benefit of some interventions is uncertain. Objective: To describe interventions aimed at reducing arterial puncture-related pain and provide an estimate of their effectiveness. Design: Systematic review and meta-analysis (PROSPERO no. CRD42020212299). Data source(s): PubMed, CINAHL EBSCO, EMBASE, the Cochrane Database of Systematic Reviews, and Scopus were searched from their inception to 7 October 2020. No temporal or language limits were applied. Methods: Published, quantitative studies on interventions aimed at reducing arterial puncture-related pain among adults were included. Screening, quality appraisal, and data extraction were undertaken independently by two reviewers. Random effects meta-analyses were performed to assess the association between interventions aimed at reducing arterial puncture-related pain and patients' perceived pain using difference in means (MD) with 95% confidence intervals (CIs). A funnel plot and Egger test were used to assess publication bias. Results: The titles and abstracts of the 2446 identified articles were screened, and 43 and 31 studies were finally included in the systematic review and meta-analysis, respectively. Interventions to reduce arterial puncture-related pain included: topical anesthetics ( n = 16), cryotherapy ( n = 9), local anesthetic infiltration ( n = 5), narrower needle gage ( n = 5), ultrasound-guided procedure ( n = 3), topical anesthetics combined with local anesthetic infiltration ( n = 1), iontophoresis using anesthetics ( n = 1), engineered blood gas syringe ( n = 1), jet injector ( n = 1), and local massage ( n = 1). Topical anesthetics [MD -0.58, 95% CI -1.00, -0.15], cryotherapy [MD -1.13, 95% CI -1.72, -0.53], and local anesthetic infiltration [MD -1.13, 95% CI -1.72, -0.53] reduced arterial puncture-related pain. No benefit was found for narrower needle gage [MD -0.07, 95% CI -0.86, 0.71] or ultrasound-guided procedure [MD -1.74, 95% CI -3.51, 0.03]. No publication bias was detected. Conclusions: Local anesthetic infiltration provided the greatest pain reduction and should be considered standard practice. Cryotherapy may be a safe, convenient alternative to local anesthetic infiltration. Topical anesthetics had limited benefit, and their lengthy time of onset makes them unsuitable for critical or emergency situations, though they may represent an option when comorbid conditions make cooling impossible. Caution must be used when interpreting these results, given the high risk of bias in the methods of included studies and the heterogeneity across the studies.